Attitude of Healthcare Providers Towards Care of People with Disabilities, in Hail Region, Saudi Arabia - Saleh KA; Alrubaiee GG; Alqalah TAH; Almoliky MA; Alrashedi H; Alkubati SA; Ahmed WA (International Journal of General Medicine)
Khalil A Saleh,1 Gamil Ghaleb Alrubaiee,2 Talal Ali Hussein Alqalah,3 Mokhtar Abdu Almoliky,4 Habib Alrashedi,5 Sameer A Alkubati,6 Waled AM Ahmed7 1Department of Medical Surgical, College of Nursing, University of Ha’il, Hail, Saudi Arabia; 2Department of Community Health, College of Nursing, University of Ha’il, Hail, Saudi Arabia, and Department of Community Health and Nutrition, Al-Razi University, Sana’a, Yemen; 3Department of Medical Surgical Nursing, College of Nursing, University of Ha’il, Ha’il, Saudi Arabia and Nursing Division, Faculty of Medicine and Health Sciences, Sana’a University, Sana’a, Yemen; 4Medical Surgical Nursing Department; College of Nursing, University of Ha’il, Hail, Saudi Arabia, and Nursing Department; Faculty of Medicine and Health Sciences; Taiz University, Taiz, Yemen; 5Medical-Surgical Nursing Department, University of Hai’l, Hail, Saudi Arabia; 6Department of Medical Surgical Nursing, College of Nursing, University of Hail, Hail City, Saudi Arabia, and Department of Nursing, Faculty of Medicine and Health Sciences, Hodeida University, Hodeida, Yemen; 7Community Health Nursing Department, Faculty of Nursing, Al-Baha University, Al-Baha, Saudi ArabiaCorrespondence: Khalil A Saleh; Waled AM Ahmed, Email dr.khalil.aden@gmail.com; wahmed@bu.edu.saBackground: Disability, whether congenital or acquired, poses significant challenges that affect individuals’ physical, mental, psychological, and social functioning. This study aimed to examine the attitudes of healthcare providers in Hai’l City towards people with disabilities.Methods: A cross-sectional design was used, involving 321 healthcare providers from the Hai’l region, employing the Scale of Attitudes towards Disabled Persons (SADP) for data collection. The data were collected through an online survey and analyzed using SPSS 26.Results: The results indicated a generally positive attitude of healthcare providers towards people with disabilities, with mean scores exceeding 89 across various groups. Older providers (over 35 years old) exhibited the highest positivity rate (92.57), although differences in age, sex, educational level, years of experience, and professional role were not statistically significant. Master’s degree holders had the highest average score (93.52), but the differences remained statistically insignificant.Conclusion: The study concludes that while healthcare providers generally have positive attitudes towards people with disabilities, there is a critical need for comprehensive training programs to enhance the quality of care provided. Future research should extend to other regions and employ qualitative methods to gain deeper insights into healthcare providers’ attitudes toward and experiences with people with disabilities.Keywords: attitudes, healthcare providers, people with disabilities, Saudi Arabia